Effects of peer review process on quality of nursing records - Ghamari-Zareh, Z; Anoosheh, M; Vanaki, Z; hajizadeh, E (Advances in Nursing & Midwifery, 2008)
Background Nursing records are considered as an indicator of care and its quality; therefore, any flaw in them can represent inadequacy of care. Peer review is an approach to authority submission by managers for nursing quality assurance. Purpose This quasi-experimental study was conducted to determine the effects of peer review process implementation on the quality of nursing records in critical cardiac wards (CCU and PCCU) at governmental hospitals of Arak in 2007. Methods 4 wards (CCU and PCCU) at 2 hospitals in Arak were selected. 2 wards with more nursing staff (25 nurses) and the other 2 with less staff (19 nurses) were chosen as case and control groups respectively. Checklists for assessing the quality of nursing records were used for data collection. 35 checklists were completed by a colleague as a pretest. Raters had been instructed regarding the assessment 1 month before the intervention. The peer review process was then performed by the raters 1 month with direct and 1 month without direct supervision of researchers. The checklists were completed again for both groups as a posttest. Results No significant difference was found between the groups in terms of demographic characteristics (age, education, financial status,…). There was no relationship between these characteristics and the quality of records. However, a significant difference was found between the groups regarding the quality of records before and after the intervention (P<0.001). Conclusion It seems that peer review process performance influences on the quality of records. Keywords: Peer review process, Quality of nursing records.